Espermatogênese e qualidade espermática em varrões pós-púberes de diferentes pesos ao nascimento. - Rafaela Costa Rubim Sacramento (2018)
In recent years, the genetic improvement has focused on increasing litter size, which has favored the occurrence of lighter piglets at birth. These animals have impaired muscle development, higher mortality rates and poor carcass quality. In addition to the effects on production traits, little is known about the impact of birth weight on reproductive traits especially in males. In this context, the quality of the males selected as semen donors in Artificial Insemination Centers (CIA) is essential to reduce the production costs of seminal doses, maximizing profits. Considering that low birth weight piglets are a reality at commercial farms, the objective of this study was to investigate the effects of low birth weight on semen quality in postpubertal males. Twenty-four males were selected according to their birth weights andsubsequently allocated to two experimental groups: High weight (HW): birth weight range from 1.80 to 2.15 kg; and Low Weight (LW): birth weight range from 0.75 to 1.10 kg. These animals were raised in separate pens for up to 300 days. Starting 180 days of age, seven animals were selected and trained for semen collection, and five ejaculates per animal were collected every 15 days for analysis of sperm quality (motility, vigor, concentration and morphology). At 300 days of age, blood samples were collected for testosterone analysis, and subsequently males were orchiectomised and the testes were collected for biometrical and histomorphometrical analyzes. To obtain the biometrical data, testes were weighed, and measures of length, width and thickness taken. In addition, small fragments of the testicularparenchyma were collected, fixed in 5% glutaraldehyde and included in glycol methacrylate resin for analyzes of spermatogenesis efficiency. Data were analyzed using SAS statistical software (version 8.0), and treatment means were compared by the Student T-test, with P < 0.05 considered significant. All biometrical and testicular measurements were lower in LW males, but birth weight did not affect spermatogenic efficiency, seminal and hormonal analysis. Even though semen analysis were similar in both experimental groups, LW males had shorter total seminiferous tubules length and a trend for lower total number of Sertoli cells per testis, which may reflect on sperm production capacity. Further studies are necessary to better understand the effects of birth weight on fertility in boars.